مداخلة علمیة حول النشر العلمى فى مصادر الوصول الحر Open Access بین التأیید والرفض - Gamal Al Dahshan (المجلة الدولية لعلوم المكتبات والمعلومات)
Scientific publishing is the scientific and important way, but it is one of themost important criteria used to estimate the level of scientific productionIt has also become one of the most important international standards forthe classification of universities, Therefore, universities and research centers areinterested in publishing the results of their scientific research in the publishedpublishing vessels, which adopt the strict scientific standardsSuch as specialized scientific journals or conference books, in order toshare knowledge and results so that research can continue and its results andobjectives will be integrated.The Free Access and Free publishing movement has emerged in the pasttwo decades as a result of its benefits in improving the flow of information. Manysocieties and institutions have embraced this movement and invested its variouscomponents in order to facilitate the flow of information not only in thesecommunities but throughout the world , This movement originated primarily as asolution to the problem of scientific communication, access to scientific researchat the time of publication or after a short period of time, and overcome theproblem of rising costs of participation in the traditional periodicals and theinability of libraries and individuals to bear the steady increase in this Field.We believe that although we believe that the scientific publishing in thesources of free access is the natural development of scientific publishing in thedigital age, we see at the same time the need to establish controls and conditionsand even standards to ensure its quality, and provide credibility to the clients andit is still not But with the revolution of electronic information and the ease of whatis described as the globalization of knowledge on the one hand, and the high costs of subscription imposed by the traditional publishing houses on the otherhand, it does not seem realistic to maintain the traditional form of publishing theexistence of the usual form, Of periodicals issued p A long-standing publishingrole for a mixed model combines the traditional model with this modelHence, openness should be open to the issue of publishing in the sourcesof free access, in addition to caution against falling into the trap of anonymouspublishers whose goal is to profit at the expense of the quality of what theypublish. This poses a challenge, as long as it exists, to find the appropriatescientific tools to disseminate scientific and research production, regardless ofthe publication model it adopts. With databases that classify reliable instrumentsand measure their performance levels based on clear criteria such as editoriallevel, peer arbitration, and the number of readings and citations obtained byperiodicals and books, the potential authors may use these tools and others toselect appropriate receptors to published their scientific output.